Implementasi Replica Volcanic Eruption Dalam Meningkatkan Kemampuan Mitigasi Bencana Erupsi Merapi Bagi Siswa Berkebutuhan Khusus Di SLBN 1 Kabupaten Sleman - Benardi, Andi Irwan; Gerar Yametis, Joshua Vincent; Azzahra, Muzakia; Fakhirah, Faustine Gilda; Budianto, Satrio Bagus; Andresheva, Satria (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
Indonesia, as a country with one of the longest volcanic chains in the world, has 127 volcanoes, with approximately 13% of all active volcanoes in the world located here. Mount Merapi is one of the most active, requiring preparedness from the community, including special needs students. SLB Negeri 1 Sleman, located in the Merapi hazard zone, faces challenges in providing effective learning media for disaster mitigation. This study proposes the use of a volcanic eruption replica as an educational tool to enhance disaster mitigation understanding and preparedness for special needs students. Through a series of stages, including planning, socialization, replica creation, implementation, and evaluation, this program successfully increased students' disaster mitigation knowledge from 30% to 85%. The results show that a multisensory approach involving a tactile replica is effective in disaster mitigation learning. The program also enhances teachers' creativity and provides important implications for the development of inclusive education and disaster mitigation policies. This research supports the need for inclusive learning media and continuous evaluation to ensure the effectiveness of disaster mitigation programs in special education schools.